Heritabilitas Sifat Ketahanan terhadap Cekaman Alelopati Gulma Teki pada Padi Gogo - Supriyanta Supriyanta (Jurnal Perlindungan Tanaman Indonesia, 2002)
Purple nut sedge (Cyperus rotundus L.) is the most difficult weed to control that produces suppressive allelochemicals to germination and early growth of upland rice. This research is aimed to identify responsive variables of upland rice varieties in competing allelopathy of purple nut sedge and estimate their heritability through mean-parents-offspring regression. The research conducted in two stages of experiment. First stage experiment is aimed to identify a critical level of purple nut sedge suppression and estimate of genetic variability among upland rice lines in responding purple nut sedge allelopathy, conducted in Completely Randomized Design with 25 lines and three replications. Experiment consisted of germination testing by tuber purple nut sedge crude extract with six concentration levels of suppression: 0, 5, 10, 15, 20 and 25%, and of competition treatment between upland rice and purple nut sedge with four levels of suppression based on sampled purple nut sedge tuber number: 0, 6, 12 and 24 tubers. Based on first stage experiment, critical level of suppression is identified at 5% of ethanol tuber extract and 6 tubers of purple nut sedge in competition treatment. Second stage experiment is screening of F1 plants and their respective parents at critical level of suppression. Plumulae length could be an effective selection criterion because of its high narrow-sense heritability (h2 = 0.73).